The reshaping of curriculum transformation to address the 21st-century skill sets and employment prospects during the Fourth Industrial Revolution era: A case of the South Africa TVET colleges - Kana, N.; Letaba, P. (South African Journal of Higher Education, 2024)
This research explores the employability of Technical and Vocational Education and Training (TVET) college graduates in the Fourth Industrial Revolution (4IR) era in South Africa. It examines the role of TVET lecturers in providing skills that are relevant to the contemporary period. The study uses qualitative research inspired by the interpretivist approach, and a purposive sampling strategy to get the perspectives of TVET lecturers and employers. It was observed that TVET lecturers play a minimal role in the development of the curriculum due to a rigid top-down approach from the Ministry of Higher Education. Companies are forming partnerships with TVET colleges by offering places for in-service training, practicals and internships. The study reveals that South African businesses have adopted 4IR-related technologies, requiring a skilled TVET force that is ready for these transformations. The findings highlight the need for regular curriculum transformation and the importance of TVET education in producing artisans, technologists and technicians that are vital for the South African economy on an ongoing basis.